Lender of last resort versus buyer of last resort: The impact of the European Central Bank actions on the bank-sovereign nexus - Viral Acharya; Diane Pierret; Sascha Steffen (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2016)
In summer 2011, elevated sovereign risk in Eurozone peripheral countries increased the solvency risk of Eurozone banks, precipitating a run on their short-term debt. We assess the effectiveness of different European Central Bank (ECB) interventions that followed - lender of last resort vs. buyer of last resort - in stabilizing the European financial sector. We find that (i) by being lender of last resort to banks via the long-term refinancing operations (LTRO), ECB temporarily reduced funding pressure for banks, but did not help to contain sovereign risk. In fact, banks of the peripheral countries used the public funds to increase their exposure to risky domestic debt, so that when solvency risk in the Eurozone worsened the run of private short-term investors from Eurozone banks intensified. (ii) In contrast, ECB's announcement of being a potential buyer of last resort via the Outright Monetary Transaction program (OMT) significantly reduced the bank-sovereign nexus. The OMT increased the market prices of sovereign bonds, leading to a permanent reversal of private funding flows to Eurozone banks holding these bonds.
Keywords: G01; G21; G28; 330; money market funds; repos; bank risk; sovereign debt; ECB